NPRL2 gene therapy induces effective antitumor immunity in KRAS/STK11 mutant anti-PD1 resistant metastatic non-small cell lung cancer (NSCLC) in a humanized mouse model - Ismail M Meraz; Mourad Majidi; Renduo Song; Feng Meng; Lihui Gao; Qi Wang; Jing Wang; Elizabeth J Shpall; Jack A Roth (eLife)
Expression of NPRL2/TUSC4, a tumor-suppressor gene, is reduced in many cancers including NSCLC. Restoration of NPRL2 induces DNA damage, apoptosis, and cell-cycle arrest. We investigated NPRL2 antitumor immune responses in aPD1R/KRAS/STK11mt NSCLC in humanized-mice. Humanized-mice were generated by transplanting fresh human cord blood-derived CD34 stem cells into sub-lethally irradiated NSG mice. Lung-metastases were developed from KRAS/STK11mt/aPD1R A549 cells and treated with NPRL2 w/wo pembrolizumab. NPRL2-treatment reduced lung metastases significantly, whereas pembrolizumab was ineffective. Antitumor effect was greater in humanized than non-humanized-mice. NPRL2 + pembrolizumab was not synergistic in KRAS/STK11mt/aPD1R tumors but was synergistic in KRASwt/aPD1S H1299. NPRL2 also showed a significant antitumor effect on KRASmt/aPD1R LLC2 syngeneic-tumors. The antitumor effect was correlated with increased infiltration of human cytotoxic-T, HLA-DR+DC, CD11c+DC, and downregulation of myeloid and regulatory-T cells in TME. Antitumor effect was abolished upon in-vivo depletion of CD8-T, macrophages, and CD4-T cells whereas remained unaffected upon NK-cell depletion. A distinctive protein-expression profile was found after NPRL2 treatment. IFNγ, CD8b, and TBX21 associated with T-cell functions were significantly increased, whereas FOXP3, TGFB1/B2, and IL-10RA were strongly inhibited by NPRL2. A list of T-cell co-inhibitory molecules was also downregulated. Restoration of NPRL2 exhibited significantly slower tumor growth in humanized-mice, which was associated with increased presence of human cytotoxic-T, and DC and decreased percentage of Treg, MDSC, and TAM in TME. NPRL2-stable cells showed a substantial increase in colony-formation inhibition and heightened sensitivity to carboplatin. Stable-expression of NPRL2 resulted in the downregulation of MAPK and AKT-mTOR signaling. Taken-together, NPRL2 gene-therapy induces antitumor activity on KRAS/STK11mt/aPD1R tumors through DC-mediated antigen-presentation and cytotoxic immune-cell activation.